Structure of the Acidobacteria homodimeric reaction center bound with cytochrome c - Dong, Shishang; Huang, Guoqiang; Wang, Changhui; Wang, Jiajia; Sui, Sen-Fang; Qin, Xiaochun (Nature communications, 2022)
Photosynthesis converts light energy to chemical energy to fuel life on earth. Light energy is harvested by antenna pigments and transferred to reaction centers (RCs) to drive the electron transfer (ET) reactions. Here, we present cryo-electron microscopy (cryo-EM) structures of two forms of the RC from the microaerophilic Chloracidobacterium thermophilum (CabRC): one containing 10 subunits, including two different cytochromes; and the other possessing two additional subunits, PscB and PscZ. The larger form contained 2 Zn-bacteriochlorophylls, 16 bacteriochlorophylls, 10 chlorophylls, 2 lycopenes, 2 hemes, 3 Fe 4 S 4 clusters, 12 lipids, 2 Ca 2+ ions and 6 water molecules, revealing a type I RC with an ET chain involving two hemes and a hybrid antenna containing bacteriochlorophylls and chlorophylls. Our results provide a structural basis for understanding the excitation energy and ET within the CabRC and offer evolutionary insights into the origin and adaptation of photosynthetic RCs. During photosynthesis, light energy is harvested by an antenna systems and delivered to the reaction centers (RCs) for charge separation and electron transfer (ET). The authors report cryo-EM structures of two forms of RC from the microaerophilic Chloracidobacterium thermophilum (CabRC), providing a structural basis for ET within the CabRC.